How is the use of research evidence in health policy perceived? A comparison between the reporting of researchers and policy-makers - Moriah E. Ellen; John N. Lavis; Einav Horowitz; Robin Berglas (BMC, 2018)
Abstract Background The use of health policy and systems research (HPSR) to inform health policy-making is an international challenge. Incorporating HPSR into decision-making primarily involves two groups, namely researchers (knowledge producers) and policy-makers (knowledge users). The purpose of this study was to compare the perceptions of Israeli health systems and policy researchers and health services policy-makers regarding the role of HPSR, factors influencing its uses and potential facilitators and barriers to HPSR, and implementation of knowledge transfer and exchange (KTE) activities. Methods A cross-sectional survey was administered to researchers and policy-makers in Israel. The survey consisted of seven closed questions. Descriptive analyses were carried out for closed-ended questions and comparative analysis were conducted between groups using the χ2 test. Results A total of 37 researchers and 32 policy-makers responded to the survey. While some views were in alignment, others showed differences. More policy-makers than researchers perceived that the use of HPSR in policy was hindered by practical implementation constraints, whereas more researchers felt that its use was hindered by a lack of coordination between knowledge producers and users. A larger percentage of policy-makers, as compared to researchers, reported that facilitators to the KTE process are in place and a larger percentage of researchers perceived barriers within the KTE environment. A larger percentage of policy-makers perceived KTE activities were in place as compared to researchers. Results also showed large differences in the perceptions of the two groups regarding policy formulation and which organisations they perceived as exerting strong influence on policy-making. Conclusions This research demonstrated that there are differences in the perceptions of knowledge producers and users about the process of KTE. Future work should focus on minimising the challenges highlighted here and implementing new KTE activities. These activities could include making the researchers aware of the most effective manner in which to package their results, providing training to policy-makers and assuring that policy-makers have technical access to appropriate databases to search for HPSR. These results underscore the need for the groups to communicate and clarify to each other what they can offer and what they require.